2016
DOI: 10.1080/14756366.2016.1193734
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the ligand binding site of CYP2C8 with CYP26A1 and CYP26B1: a structural basis for the identification of new inhibitors of the retinoic acid hydroxylases

Abstract: The CYP26s are responsible for metabolizing retinoic acid and play an important role in maintaining homeostatic levels of retinoic acid. Given the ability of CYP2C8 to metabolize retinoic acid, we evaluated the potential for CYP2C8 inhibitors to also inhibit CYP26. In vitro assays were used to evaluate the inhibition potencies of CYP2C8 inhibitors against CYP26A1 and CYP26B1. Using tazarotenic acid as a substrate for CYP26, IC 50 values for 17 inhibitors of CYP2C8 were determined for CYP26A1 and CYP26B1, rangi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 102 publications
(147 reference statements)
0
14
0
Order By: Relevance
“…9, C and D). However, the IC 50 values, 124 mM (26-594; 95% confidence intervals) with ketoconazole and 3.8 mM (1.8-8.1; 95% CI) with talarozole, were much higher than the IC 50 values observed with CYP26A1 (,10 nM for talarozole and 0.55 mM for ketoconazole) and CYP26B1 (,10 nM for talarozole and 0.59 mM for ketoconazole) (Thatcher et al, 2011;Diaz et al, 2016;Foti et al, 2016a).…”
Section: Cyp26c1 As a Retinoid Hydroxylasementioning
confidence: 70%
“…9, C and D). However, the IC 50 values, 124 mM (26-594; 95% confidence intervals) with ketoconazole and 3.8 mM (1.8-8.1; 95% CI) with talarozole, were much higher than the IC 50 values observed with CYP26A1 (,10 nM for talarozole and 0.55 mM for ketoconazole) and CYP26B1 (,10 nM for talarozole and 0.59 mM for ketoconazole) (Thatcher et al, 2011;Diaz et al, 2016;Foti et al, 2016a).…”
Section: Cyp26c1 As a Retinoid Hydroxylasementioning
confidence: 70%
“…This opens the possibility that CYP26B1 may have other substrates. Such a speculation is strengthened by the likely differences in active sites of the two enzymes, revealed by their different responses to various selective inhibitors [38].…”
Section: Discussionmentioning
confidence: 99%
“…1). Foti et al (2016) reported that the degradation of candesartan cilexetil was minimal upon incubation with CYP2C8, with no appreciable formation of an ester-hydrolyzed product. Computational docking simulation showed that candesartan cilexetil strongly inhibited the CYP2C8-mediated amodiaquine metabolism (IC 50 = 0.50 µM; Walsky et al, 2005), without interacting with the heme.…”
Section: Discussionmentioning
confidence: 99%